Les militantes yorubas se mettent en scène : la politisation du corps habillé à l’époque coloniale - Sara Panata (Genre & Histoire)
From the 1920s on, photography emerged in the south of Nigeria as a means to immortalize crucial events in private and public life. Between 1920 and 1960, in a period of significant political change, the dressed and staged body became a political tool in the hands of Yoruba female activists who used photography to deliver the messages they sought to spread. This article uses colonial photographs to analyse the cultural and political dynamics revealed by women’s poses and to understand how corporal codes were used to convey cultural, religious or political identities.